Transient osteoporosis of the knee in pregnancy: A case report and literature review - Thomas Ferenc, MD; Andro Matković, MD; Nikolina Jurjević, MD; Vitorio Perić, MD; Božidar Šebečić, MD, PhD; Vinko Vidjak, MD, PhD (Radiology Case Reports)
Transient osteoporosis (TO) is a self-limiting bone disorder with a benign clinical course and unknown etiology, typically manifesting in the third trimester of pregnancy. There are only a few documented cases of TO in pregnant women involving the knee joint. We report a 38-year-old female patient in the third trimester of pregnancy who presented with an 8-week history of progressive worsening of the right knee pain. Clinical and magnetic resonance imaging findings were suggestive of TO with complete resolution of symptoms and imaging findings within several months following the onset of the symptoms. Clinicians need to include TO in their differential diagnosis when treating pregnant women with knee pain.